Tax thy neighbour: Corporate tax pass-through into downstream consumer prices in a monetary union - Luca Dedola; Chiara Osbat; Timo Reinelt (European Central Bank (ECB), 2022)
We estimate the response of product-level retail prices to changes in the corporate tax rates paid by wholesale producers (pass-through). Under perfect competition in goods and factor markets, pass-through of corporate taxes should be zero, and their incidence mainly falls on factor prices. We use variation in tax rates across time and space in Germany, where municipalities set the local business tax once a year, to provide estimates of tax pass-through into the retail prices of more than 125,000 food and personal care products sold across Germany. By leveraging 1,058 changes in the local business tax rate between 2013 and 2017, we find that a one percentage point tax increase results in a 0.4% increase in the retail prices of goods produced by taxed firms and purchased by consumers in the rest of Germany, who thus end up bearing a substantial share of the tax burden. This finding suggests that manufacturers may exploit their market power to shield profits from corporate taxes, complicating the analysis of the redistributive effects of tax reforms. We also explore various dimensions of heterogeneity in pass-through related to market power, including producer size, market shares, and retail store types. While producer heterogeneity does not seem to matter, the significant passthrough of corporate taxes to consumer prices in the low in ation period covered by our sample is mostly due to price changes in supermarkets and hypermarkets.
Keywords: F12; F45; E13; H71; L11; 330; corporate taxes; producer pass-through to retail prices; imperfect competition; vertical interactions